Diagnostic algorithms in Charcot-Marie-Tooth neuropathies: experiences from a German genetic laboratory on the basis of 1206 index patients - Rudnik-Schöneborn, Sabine; Tölle, D.; Senderek, J.; Eggermann, K.; Elbracht, M.; Kornak, U.; Hagen, M. von der; Kirschner, J.; Leube, B.; Müller‐Felber, W.; Schara, U.; Au, K. von; et al. (Clinical genetics, 2016)
We present clinical features and genetic results of 1206 index patients and 124 affected relatives who were referred for genetic testing of Charcot-Marie-Tooth (CMT) neuropathy at the laboratory in Aachen between 2001 and 2012. Genetic detection rates were 56% in demyelinating CMT (71% of autosomal dominant (AD) CMT1/CMTX), and 17% in axonal CMT (24% of AD CMT2/CMTX). Three genetic defects (PMP22 duplication/deletion, GJB1/Cx32 or MPZ/P0 mutation) were responsible for 89.3% of demyelinating CMT index patients in whom a genetic diagnosis was achieved, and the diagnostic yield of the three main genetic defects in axonal CMT (GJB1/Cx32, MFN2, MPZ/P0 mutations) was 84.2%. De novo mutations were detected in 1.3% of PMP22 duplication, 25% of MPZ/P0, and none in GJB1/Cx32. Motor nerve conduction velocity was uniformly <38 m/s in median or ulnar nerves in PMP22 duplication, >40 m/s in MFN2, and more variable in GJB1/Cx32, MPZ/P0 mutations. Patients with CMT2A showed a broad clinical severity regardless of the type or position of the MFN2 mutation. Out of 75 patients, 8 patients (11%) with PMP22 deletions were categorized as CMT1 or CMT2. Diagnostic algorithms are still useful for cost-efficient mutation detection and for the interpretation of large-scale genetic data made available by next generation sequencing strategies.
First published: 08 April 2015
Gesehen am 06.05.2020